2020
DOI: 10.1002/uog.21957
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prospective measurement of outflow tracts in prediction of coarctation of the aorta

Abstract: Objectives Prenatal diagnosis of coarctation of the aorta (CoA) is associated with reduced mortality and morbidity, however, accurate prenatal prediction remains challenging. To date, studies have used retrospective measurements of the outflow tracts to evaluate their potential to predict CoA. Our primary objective was to evaluate prospectively acquired measurements of the outflow tracts in fetuses with prenatally suspected CoA. A secondary aim was to report the postnatal prevalence of bicuspid aortic valve in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 38 publications
7
22
1
1
Order By: Relevance
“…However, as in our series, other studies did not observe differences for functional parameters (flow at the aortic arch and FO) between CoAo and no CoAo fetuses [18,20,24]. We also did not find differences for PLSVC according to postanal outcome (CoAo vs. no CoAo), similarly to other groups [18,22,24,25,33]. Nevertheless, Morgan et al [20] found more cases of PLSVC in fetuses with CoAo compared to normal cases, although in the multivariate analysis, it was not statistically significant.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…However, as in our series, other studies did not observe differences for functional parameters (flow at the aortic arch and FO) between CoAo and no CoAo fetuses [18,20,24]. We also did not find differences for PLSVC according to postanal outcome (CoAo vs. no CoAo), similarly to other groups [18,22,24,25,33]. Nevertheless, Morgan et al [20] found more cases of PLSVC in fetuses with CoAo compared to normal cases, although in the multivariate analysis, it was not statistically significant.…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies have proposed some morphological and functional fetal echocardiographic parameters, and even multiparameter scoring systems in order to improve the prenatal prediction of the likelihood of postnatal confirmation of CoAo [18][19][20][21][22][23][24][25][30][31][32][33]. The current study is the largest to prospectively assess the capability of a multiparameter scoring system to predict CoAo in fetuses with ventricular and great vessel disproportion with right dominance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations